FRACTAL ANALYSIS IN NEUROANATOMY AND NEUROHISTOLOGY - Zaletel, Ivan V; Puškaš, Nela (Medicinski podmladak, 2016)
For decades research in the field of neuroscience involves the use of different methods which allow us to visualize the elements within the nervous system, primarily nerve cells. An integral part of such research is the quantification of the analyzed image, which largely relies on the use of traditional mathematical methods based on linear analysis. On the other hand, fractal analysis a form of non-linear analysis, can give us more detailed information about the complexity of some anatomical or histological structures, which classical Euclidean geometry is not able to adequately describe and quantify. This review aims to show the possibilities of fractal analysis in neuroanatomy and neurohistology, i.e. in the analysis of images of different components of the nervous system and nervous tissue.